THE EFFECTIVE ROLE AND PROSPECTS OF ARTIFICIAL INTELLIGENCE IN LEARNING LANGUAGE - G‘ulomova Sevinchkxon Muxiddin qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article highlights the invaluable help of artificial intelligence (AI) technologies for language learners and their effectiveness. The main purpose of the article is to examine the significant impact of applications, programs and bots created using artificial intelligence in the language learning process. The methodology of this study was a peer-reviewed analysis of several scientific articles and real-life examples. The results are very positive, AI technologies increase motivation for language learners, have a positive impact on their personal approach, and are also of great importance for the culture of communication. These technologies open many doors not only for learners, but also for teachers.